2008
DOI: 10.1007/s00267-008-9122-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rainfall Regime and Slope on Runoff in a Gullied Loess Region on the Loess Plateau in China

Abstract: Runoff was measured from seven plots with different slopes nested in Tuanshangou catchment on the Loess Plateau to study effect of slopes on runoff in relation to rainfall regimes. Based on nine years of field observation and K-mean clusters, 84 rainfall events were grouped into three rainfall regimes. Rainfall regime A is the group of events with strong rainfall intensity, high frequency, and short duration. Rainfall regime C consists of events with low intensity, long duration, and infrequent occurrence. Rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 42 publications
4
40
2
1
Order By: Relevance
“…The reason for this difference is probably because of the quick convergence of runoff from the slope (10°) in our study. Chaplot and Le Bissonnais (2000) and Fang et al (2008) found also that the larger slope gradient could lead to higher flow velocity and increased runoff generation capacity. Similar temporal patterns were shown between TSS and TP.…”
Section: Temporal Changes In Pollution During Rainingmentioning
confidence: 96%
“…The reason for this difference is probably because of the quick convergence of runoff from the slope (10°) in our study. Chaplot and Le Bissonnais (2000) and Fang et al (2008) found also that the larger slope gradient could lead to higher flow velocity and increased runoff generation capacity. Similar temporal patterns were shown between TSS and TP.…”
Section: Temporal Changes In Pollution During Rainingmentioning
confidence: 96%
“…Crusting is easily formed for the loess-textured soils on the Loess Plateau, and the hard layer on the soil surface increases its antierodibility (Luk et al 1989, Fang et al 2008b. Runoff scour and crusting formation during rainfall bred a temporal lack of sediment that produced a certain percentage of type I floods and clockwise hysteresis loops in slope zones (Table 3; Fig.…”
Section: Sediment Origin and Sediment Dynamicsmentioning
confidence: 99%
“…For the total erosion, Jin (1995) presented that there was a critical slope which made erosion from strong to weak, but it is not a constant value, which changed with other factors such as soil property, rainfall intensity, etc. (Fang et al 2008;He et al 2012). Rill node, rill number and distance of the longest rill to the top of the slope were also used to analyze the characteristics of rill formation (Table 3).…”
Section: Effects Of Slope Gradient On the Characteristics Of Rill Formentioning
confidence: 99%